2012
DOI: 10.3122/jabfm.2012.06.120128
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perspective on Watchful Waiting/Active Surveillance for Localized Prostate Cancer

Abstract: Objective To describe prostate cancer treatment decision making, focusing on knowledge and attitudes toward observation, known as watchful waiting (WW) or active surveillance (AS), and reasons for not choosing WW/AS. Methods Semistructured in-person interviews were conducted with 21 men (14 black; 7 white) with recently diagnosed localized prostate cancer. Results All cancers were detected by prostate-specific antigen screening; 14 men had low-risk disease. Nineteen chose surgery or radiation treatment. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
89
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(92 citation statements)
references
References 52 publications
2
89
0
1
Order By: Relevance
“…We think this result is plausible since so many controversies and uncertainties exist surrounding the myriad treatment options for LPC and a lack of consensus even among experts regarding the best decision. 9,10,13 Another possible explanation is that when men's overall knowledge of treatment side effects and survival benefit is so low, it may not reach the threshold at which a positive impact on decisionmaking difficulty can be observed. In fact, Orom et al 12 also reported that increased knowledge of LPC was associated with greater decision-making difficulty.…”
Section: 29mentioning
confidence: 99%
See 2 more Smart Citations
“…We think this result is plausible since so many controversies and uncertainties exist surrounding the myriad treatment options for LPC and a lack of consensus even among experts regarding the best decision. 9,10,13 Another possible explanation is that when men's overall knowledge of treatment side effects and survival benefit is so low, it may not reach the threshold at which a positive impact on decisionmaking difficulty can be observed. In fact, Orom et al 12 also reported that increased knowledge of LPC was associated with greater decision-making difficulty.…”
Section: 29mentioning
confidence: 99%
“…Since no validated knowledge scale about LPC is available in the literature, we constructed our own knowledge scale based on the literature and qualitative studies. 9,10,32 Finally, our data were from 1 geographic location that may not be representative of other locations.…”
Section: 29mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in a recent study among Indian patients Xu et al (2012) indicated that most men were unaware of treatment options and the outcomes for prostate cancer.…”
Section: )mentioning
confidence: 99%
“…8,16 The survey asked men to report their treatment choice, reasons for the choice, and what treatment options were offered and recommended by their physicians. 5 In addition, patients were asked the following 2 questions: "How long do you expect you would live without any treatment for your prostate cancer?"…”
Section: Survey Instrumentmentioning
confidence: 99%